PROGRAMA DE EDUCAÇÃO PELO TRABALHO PARA A SAÚDE (PET-SAÚDE) E A FORMAÇÃO DO NUTRICIONISTA NUM CAMPUS DE INTERIORIZAÇÃO - Ana Eliza Port Lourenço; Amábela de Avelar Cordeiro; Jane de Carlos Santana Capelli; Renata Borba de Amorim Oliveira; Priscila Vieira Pontes; Maria Fernanda Larcher de Almeida; Laís Buriti de Barros (Universidade do Estado do Rio de Janeiro, 2017)
Objectives: With a focus on nutritionists' education, this article analyzes the experience of a team of the Education through Work for Health Program (PET-Saúde) in the Federal University of Rio de Janeiro, Macaé Campus, effective between 2012 and 2014. Methodology: This team developed activities about nutrition in the municipal health system. PET-Saúde was created in the context of university extended education courses, and it is understood as an integral and inseparable part of higher education. Educational and training activities for the team were based on the Paulo Freire's theoretical framework on problematization-reflection. Content analysis was performed to assess members' testimonials about their experience in PET-Saúde. Results and discussion: Practice-based learning and knowledge exchange were the main experience benefits to the education of all group members. These benefits contribute to nutritionists' education, because they narrow the distance between academic education and professional practice. This experience fostered greater social engagement, autonomy, leadership, criticality and broadening of student's perception on health and nutrition issues within the Brazilian Health System. One needs to think about the repercussions of the experience of PET-Saúde, especially given the current scenario of adjustment of Brazilian higher education. Conclusions: Curricular and pedagogical changes in nutritionists' education may be rethought, based on this experience, in order to better incorporate social demands and promote education with a transformative potential. In this sense, this experience contributes to the non-hegemonic movement against the professional education model focused on the capitalist marke DOI: 10.12957/demetra.2017.26214